Implementing and working with the Youth Criminal Justice Act across Canada - Alain, Marc; Corrado, Raymond R.; Reid, Susan (University of Toronto Press, 2016)
"Since its implementation in 2003, the Youth Criminal Justice Act has been the subject of intense political and scholarly debate. A complicated mixture of provisions intended to provide harsher punishments for serious violent crimes while encouraging positive, non-punitive interventions in less serious cases, its impact on the youth justice system remains controversial. Implementing and Working with the Youth Criminal Justice Act across Canada provides the first comprehensive, province-by-province analysis of how each Canadian jurisdiction has implemented the Act in accordance with its own history, traditions, and institutional arrangements. Drawing on in-depth interviews with probation officers, counselors, educators, and social workers, the contributors use the experiences of practitioners to offer a new analytical perspective on a complicated and contentious aspect of the Canadian justice system. Their conclusions provide vital policy and program information for researchers, practitioners, and policy makers concerned with Canada's youth justice systems."--